Implementation on Evolved Packet Core and Wireless Network End-to-End Tracing - Zhe Wang; Hongdong Xu; Limin Zhao (Dianxin kexue)
In the 4G network, because the flat network structure, wireless access side cannot independently to realize the analysis of user tracking and optimization. In order to solve the above problem, based on 3GPP protocol, the construction of EPC and LTE wireless cooperative tracking processing mechanism was proposed, the optimization scheme was put forward to solve the application problem of different manufacturers scene, and to meet the current network user tracking and optimization analysis of demand, a platform for further user based localization problem and the key security was provided.